2010
DOI: 10.4049/jimmunol.1001535
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Restricts Memory T Cell Inflation during Cytomegalovirus Infection

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 84 publications
5
47
0
Order By: Relevance
“…We adopted this approach to ensure adequate sampling depth and minimize bias arising from lack of coverage, which would lead to an underestimation of frequency differences between individual clonotypes. The TRBV1/TRBJ2-1 and TRBV16/TRBJ2-5 gene rearrangements selected for this study are prevalent within memory CD8 + T-cell populations specific for the M38 SSPPM-FRVP/H-2K b (unpublished data) and IE-3 RALEYKNL/H-2K b (9) epitopes derived from murine cytomegalovirus, respectively. Naïve CD8 + T cells were stringently defined by polychromatic flow cytometry according to the expression of multiple lineage and phenotypic markers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We adopted this approach to ensure adequate sampling depth and minimize bias arising from lack of coverage, which would lead to an underestimation of frequency differences between individual clonotypes. The TRBV1/TRBJ2-1 and TRBV16/TRBJ2-5 gene rearrangements selected for this study are prevalent within memory CD8 + T-cell populations specific for the M38 SSPPM-FRVP/H-2K b (unpublished data) and IE-3 RALEYKNL/H-2K b (9) epitopes derived from murine cytomegalovirus, respectively. Naïve CD8 + T cells were stringently defined by polychromatic flow cytometry according to the expression of multiple lineage and phenotypic markers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, therapeutic vaccination during persistent LCMV infection, in combination with either anti-PD1 or anti-IL-10 antibodies, improves LCMV-specific T cell immunity and consequently leads to a decrease in viral load [73,74]. Blocking of IL-10 in CMV-infected mice enhances the expansion of functional memory T cells and results in reduced viral load in chronic and latent infection [53]. Based on the enhanced control of established persistent LCMV infection and restoration of virus-specific immunity when PD-1 and IL-10 are blocked [75], the combination of these antibodies might have a stronger impact on vaccineinduced immunity and clinical outcome in humans.…”
Section: Immunotherapy Of Chronic Viral Infections -A Foreseeable Futmentioning
confidence: 96%
“…Notably, EBV and CMV express genes that encode for a viral homolog of IL-10 that has the same immunosuppressive potency as human IL-10 [51]. IL-10 protein that is encoded by the CMV gene that encodes IL-10 suppresses recognition of latently infected myeloid progenitor cells by CD4 + T cells [52], and this effect can be relieved by blocking the binding of viral IL-10 to the IL-10 receptor [53]. In addition, it has been reported that chronic active EBV in EBV-infected T cells increases transcription of Il10 and Tgfb [54].…”
Section: Hbv Infectionmentioning
confidence: 99%
“…The cytokines IL-7 and IL-15, which are important for homeostatic proliferation of memory CD8 + T cells, have potent proliferative properties for HCMVspecific T cells in vitro [42], but their precise role for memory T cell inflation in an in vivo setting remains to be elucidated. Another important cytokine is IL-10, which clearly restricts inflation of T cells in the chronic phase of CMV infection by unknown mechanisms [43].…”
Section: Cytokinesmentioning
confidence: 99%